1989
DOI: 10.1007/bf00610445
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in the visual pigments of deep-sea fishes

Abstract: Visual pigments in the rods of 38 species of deep-sea fish were examined by microspectrophotometry. 33 species were found to have a single rhodopsin with a wavelength of maximum absorbance (lambda max) in the range 470-495 nm. Such visual pigments have absorbance maxima close to the wavelengths of maximum spectral transmission of oceanic water. 5 species, however, did not conform to this pattern and visual pigments were found with lambda max values ranging from 451 nm to 539 nm. In 4 of these species two visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 35 publications
8
102
1
Order By: Relevance
“…Candidate sites for spectral tuning that are identified in the text are indicated by an asterisk. The λ max values (nm) of the rod visual pigments were measured by microspectrophotometry (Partridge et al 1988 ;Partridge 1989 ;Partridge et al 1989 ;Archer et al 1992 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Candidate sites for spectral tuning that are identified in the text are indicated by an asterisk. The λ max values (nm) of the rod visual pigments were measured by microspectrophotometry (Partridge et al 1988 ;Partridge 1989 ;Partridge et al 1989 ;Archer et al 1992 …”
Section: Resultsmentioning
confidence: 99%
“…laticeps (Partridge et al 1988 ;Partridge 1989 ;Partridge et al 1989). This contrasts with values of around 500 nm found in shallow living species (Lythgoe 1972) and in the eel ' freshwater ' pigment.…”
Section: (B) Spectral Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…This length is effectively doubled to 148 mm by the presence of the tapetum. With a typical absorption coefficient k for deep-sea fishes of 0.064 mm 21 [26,27], this leads to 12e 2kl ¼ 0.9999. Thus, assuming that all layers are functional (which they may not be [28]), the banked retina of the escolar can significantly enhance the sensitivity of the eye.…”
Section: (B) Sensitivitymentioning
confidence: 99%
“…Electrophysiological, morphological, and some behavioral studies have indicated that most deep-sea fishes have limited sensitivity to longer wavelengths (Partridge et al 1988, Douglas & Partridge 1997, Widder et al 2005). However, a few genera (Pachystomias, Aristostomias, and Malacosteus) in 1 family of meso-/bathypelagic fishes, are known to produce far-red bioluminescence and to have longwave visual sensitivity (O'Day & Fernandez 1974, Widder et al 1984, Bowmaker et al 1988, Partridge et al 1989, and the possibility cannot be discounted for some others (Douglas et al 2002). Widder et al (2005) demonstrated that the deep-sea fish Anoplopoma fimbria (sablefish, Anoplopomatidae) responded to red light in situ even though this species has a maximum visual sensitivity at 491 nm (Ali & Wagner 1975).…”
Section: Introductionmentioning
confidence: 99%